Kajian naskhah undang-undang adat Melayu di London - Jelani Harun, (Universiti Kebangsaan Malaysia, 2008)
The Malay adat laws (Malay customary laws) have existed long ago in the Malay society and have been passed down from generation to generation orally. What follows is a written law that became a rule that society has to abide by. The importance of Malay adat laws is reflected in the large number of manuscripts that are available. In spite of its importance, a serious study (especially based on Jawi manuscripts kept in London) is still lacking and inadequate. Thus, this paper aims to discuss this problem with the following objectives: to trace the early British interest in the Malay adat law writings in addition to identify specific features of the concept of the Malay adat law and to evaluate the forms of interaction between the Malay tradition and Islamic thought concerning the concepts of justice